Strategies to Prevent Neuronal Entry and Central Nervous System Invasion of the Rabies Virus: Emerging Targets for Antiviral Drug Development (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Rabies is one of the most fatal viral infections affecting the central nervous system, with nearly 100% mortality once clinical symptoms appear. The disease is caused by the neurotropic rabies virus and is primarily transmitted through bites from infected animals. Current preventive strategies rely on vaccination and post-exposure prophylaxis; however, no effective antiviral therapy is available once neuronal infection has occurred. A critical step in rabies pathogenesis is the virus's ability to enter peripheral neurons and subsequently travel toward the central nervous system through retrograde axonal transport. Therefore, preventing neuronal entry and blocking neuro invasion represent promising therapeutic strategies. This review highlights the molecular mechanisms involved in rabies virus entry into neurons, the role of viral glycoproteins in host-cell interactions, and potential antiviral approaches aimed at preventing neuronal infection and central nervous system invasion. Emerging strategies, including receptor blockers, glycoprotein inhibitors, monoclonal antibodies, and innovative drug delivery systems, are also discussed. Understanding these mechanisms may contribute to the development of novel therapeutic agents capable of preventing rabies progression after exposure and improving future therapeutic outcomes.
Keywords: Rabies virus; Neuro invasion; Neuronal entry; Antiviral therapy; viral glycoprotein; Drug delivery systems